METHODS OF EVALUATING THE QUALITY OF HOUSEHOLD SERVICES AND WAYS TO IMPROVE IT - Artikova Shoxida Ilyasovna (Scholar Express Journals, 2022)
The article analyzes ways of improving the methods of assessing the quality of household services, highlights organizational, economic and social factors, and presents scientific, methodological and practical suggestions for improving the quality of services
Keywords: Quality assessment; network; corporation; criteria